Computer-aided drug design and the biological evaluation of anti-cancer drugs - Moorad, Razia (Division of Medical Biochemistry, 2016)
Computer-aided drug design has become a promising alternative to high-throughput screening by identifying potential hits in silico for in vitro evaluation. In this study a combination of ligand-based and structure-based virtual screening was performed to identify in silico hits. This was based on finding similar inhibitors to 6-amino-4-(4-phenoxyphenylethylamino) quinazoline, a potent inhibitor of the Nuclear Factor kappa B (NF-κB), a transcription factor that has a pivotal role in cancer survival and Pentamidine, an anti-parasitic drug that has recently been demonstrated to possess tumour-killing activity. A hierarchical methodology consisting of a similarity search followed by structure-based virtual screening of the ZINC database was performed. In order to perform the docking studies, binding sites for 6-amino-4-(4-phenoxyphenylethylamino) quinazoline on the NF-κB/IκBα complex were identified through blind docking. In addition, the National Cancer Institute (NCI) database was screened, utilising existing structure-activity relationship data from literature. A pharmacophore search was designed to test the hypothesis of the structural features necessary for activity as seen with quinazoline inhibitors of NF-κB. No virtual hits from the ZINC database were confirmed with in vitro activity. On the other hand, three compounds identified from the pharmacophore search were confirmed to inhibit cancer cell proliferation in vitro, with compound NSC727152 demonstrating the most potent activity. In order to determine if NSC727152 acted similarly to 6-amino-4-(4-phenoxyphenylethylamino) quinazoline by inhibiting NF-κB, the effects of NSC727152 on the expression of NF-κB targeted genes, including the Growth Arrest and DNA Damage 45 (GADD45) α and γ and the Interleukin 6 (IL-6) genes were evaluated. GADD45 α and γ have been shown to be regulated by NF-κB during cancer progression and aberrant IL-6 gene expression has been implicated in cancer progression and mortality and its expression is at least partially mediated via constitutive activation of NF-κB. In this study, it has been demonstrated that GADD45 α and γ are upregulated after treatment with NSC727152. A down-regulation of the IL-6 promoter activity and mRNA expression in cancer cells treated with NSC727152 has also been demonstrated in this study. However, no hits similar to Pentamidine were confirmed with in vitro activity. In conclusion, the compound NSC727152 has been shown to inhibit NF-κB and further analysis is necessary to determine its full potential as an NF-κB inhibitor.